A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMK TARUNA PEKANBARU IN WRITING RECOUNT TEXTS - Eksa, Ghenie Filosofie Estiarhariani; Gultom, Effendy; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research aims to find out the ability level of the second year students of SMK Taruna Pekanbaru in writing recount texts. The population of this research are the second year students of SMK Taruna Pekanbaru. The number of sample is 21 students who are chosen by using cluster random sampling technique. The data are collected using a writing test which contains one topic about â€œunforgettable experienceâ€. The results of the data analysis showed that the mean score of the studentsâ€™ ability in writing recount texts is 72.14. It can be stated that the ability of the second year students of SMK Taruna Pekanbaru in writing recount texts is good. Based on the result of the studentsâ€™ ability in each writing aspect, the lowest score is in grammar aspect (64.68) and the highest score is in fluency aspect (80.55).Keywords: Study, Writing Ability, Recount Text.